Holothuria grisea agglutinin (HGA): the first invertebrate lectin with anti‐inflammatory effects. (3rd September 2012) - Moura, Raniere da M.; Aragão, Karoline S.; de Melo, Arthur A.; Carneiro, Rômulo F.; Osório, César B. H.; Luz, Patricia B.; de Queiroz, Alexandre F. S.; dos Santos, Elizeu A.; de Alencar, Nylane M. N.; Cavada, Benildo S.
Abstract: Holothuria grisea agglutinin (HGA) is a dimeric lectin of molecular mass 228 kDa by gel filtration with monomers of 105 kDa by SDS‐PAGE. The lectin is highly thermostable as it retains full activity for 1 h at 70 °C. Unlike other lectins purified from marine invertebrates, the hemagglutination activity of HGA does not require any divalent metal ions. The affinity analysis of HGA showed that only mucin was able to inhibit the hemagglutinating activity. HGA administered intravenously was tested in classical models of nociception and inflammation. HGA was able to inhibit neutrophil migration into the peritoneal cavity induced by carrageenan. This inhibitory effect was 68% at a dose of 1 mg/kg. In acetic acid‐induced writhing tests, a significant antinociceptive effect was observed by treatment with HGA (0.1; 1 or 10 mg/kg) reducing constrictions by 27, 90 and 84%, respectively. In formalin tests, HGA at a dose of 10 mg/kg showed antinociceptive effect only in the inflammatory phase (phase 2). Nevertheless, in hot‐plate tests, HGA did not show any nociceptive effect. In rota‐rod and open‐field tests, HGA did not alter the animals' behavior. The treatment with HGA 10 mg/kg presented diminished myeloperoxidase activity activity (81.6% inhibition) and raised the circulating levels of NO by 50.4% when compared with the carrageenan group. HGA has demonstrated the ability to modulate the inflammatory response in models of inflammation in vivo. HGA is the first marine invertebrate lectin that showed an anti‐inflammatory effect. This finding opens a new perspective on the potential of lectins from the marine environment.